Clinicopathological retrospective analysis of thymoma in Serbia: A single center experience - Samardžić, Natalija; Jovanović, Dragana; Marković-Denić, Ljiljana; Šarac, Sanja; Škodrić-Trifunović, Vesna; Stojšić, Jelena; Stjepanović, Mihailo; Popević, Spasoje; Ilić, Branislav; Ćeriman, Vesna; Roksandić Milenković, Marina; Gajić, Milija; et al. (Vojnosanitetski pregled, 2021)
Background/Aim. Thymoma is the most common mediastinal tumor. The treatment procedures are based on the results from the research of retrospective studies because they are not frequent tumors. The aim of this work was to define common clinical features, therapeutic aspects, survival and recurrence free survival. Methods. This study was performed in the Clinic for Pulmonology, Clinical Centre of Serbia, Belgrade from January 1993 to December 2013. We analyzed 62 patients with histopathologically proven thymoma. The results were obtaind from medical history, physical exam, chest X-ray and/or computed tomography and operational findings or diagnostic procedure reports. Thymomas were clasiffied according to the World Health Organization classifying system, based on histopathological findings, and staged according to the Masaoka-Koga staging system. Results. There were more female (54.8%) patients. Patients were mostly in the seventh decade of life. One third (29%) of the patients were asymptomatic. Cough was the dominant symptom. Myasthenia gravis was the most common paraneoplastic syndrome (12.9%). Solitary tumor was the most common in our patients (61.3%), as well as the tumors larger than 5 cm (52.5%), and noninvasive thymomas (52.5%). The majority of patients (40%) were in the stage I of the disease. The operative approach was conducted in most of the patients (88.7%). A statistically significant difference in survival was in women, patients with solitary tumor, non-invasive thymomas, patients in the stage I of the disease, and those who were operated. The dimension of the tumor mass approached the conventional level of significance. Conclusion. In patients with thymomas, statistically significant survival rate predictors are gender, presence of solitary tumor mass, tumor invasiveness, clinical stage and surgical treatment of the disease.